A new angle to control concentration profiles at electroactive biofilm interfaces: Investigating a microfluidic perpendicular flow approach. (1st November 2022) - Gong, Lingling; Khodaparastasgarabad, Nastaran; Hall, Derek M.; Greener, Jesse
Highlights: Concentration profiles above electroactive biofilms (EABs) change with microflow conditions. Inhomogeneous concentration profiles above EABs influence reaction kinetics. Tangential flow across an EAB increases concentration profile heterogeneity. Perpendicular flow with electrode adjustments remove most heterogeneity. Abstract: To meet the growing interest in bioelectrochemical flow systems, we propose a new microfluidic-based approach to studying electroactive biofilms (EABs). Despite the near limitless range of available channel designs and reaction control sequences, one of the main drawbacks compared rotating disk electrode systems, is the typical non-uniformity in the concentration boundary layer above the EAB outer surface. This drawback undermines the claim that microfluidic electrochemical systems provide pristine operating conditions. We address this challenge through the use of simulations, backed by experiments, to investigate microfluidic design parameters (flow orientation, counter-electrode placement, and channel dimensions) that significantly enhance the boundary layer uniformity across the entire EAB surface. Simulations confirmed that the large asymmetries in the boundary layer thickness between the upstream and downstream edges in conventional tangential flow systems are strongly reduced by transitioning to a perpendicular flow orientation. Further optimizations in electrode placement and channel design nearly erased the remaining inhomogeneity in the boundary layer thicknesses.